The use of 4.5% hypertonic saline challenge test in diagnosing asthma in children with chronic recurrent cough - Bambang Supriyatno; Dina Medina; Alan R Tumbelaka; Nastiti N Rahajoe (Paediatrica Indonesiana, 2005)
Background The 4.5% hypertonic saline (HS) challenge test hasseveral benefits compared to histamine challenge test as gold stan-dard. Saline is an inexpensive non-pharmacological substancewhich is relatively safe. Its mechanism in inducing bronchospasmresembles that of asthma. Moreover, it can easily be made in amodest medical laboratory.Objective To determine the ability of 4.5% HS challenge test com-pared to histamine challenge test in diagnosing asthma in childrenwith chronic recurrent cough (CRC).Methods This study was a diagnostic test on children with CRCaged 6 to 14 years, conducted in outpatient clinic of Department ofChild Health, Cipto Mangunkusumo Hospital, Jakarta. All subjectsunderwent lung function tests. Subjects whose FEV 1 was <80% werediagnosed as asthmatic and underwent the 4.5% HS challenge testonly. Those whose FEV 1 was 80% underwent the histamine chal-lenge test followed by the 4.5% HS challenge test one or two weekslater. Test results were expressed as positive or negative. Based onthe results, we calculated the sensitivity, specificity, predictive val-ues, and likelihood ratios of the 4.5% HS challenge test.Results Forty-five subjects, consisting of 22 boys and 23 girls,were enrolled. The average age of subjects was 9 years old. Atopichistory in the family or in subjects themselves was found in 80% ofsubjects. Eight subjects had FEV 1 of <80%. Forty-four subjectswere diagnosed with asthma based on a baseline FEV 1 of <80%or a positive histamine provocation test. Thirty-seven subjects hada positive 4.5% HS challenge test; all had asthma. Sensitivity andspecificity of the 4.5% HS challenge test were 84.1% and 100.0%,respectively; the positive and negative predictive values were100.0% and 12.5%, respectively. The positive likelihood ratio wasinfinite and negative likelihood ratio was 0.16.Conclusion The 4.5% hypertonic saline challenge test can be usedas an alternative bronchial provocation test in diagnosing asthma inchildren with CRC. Further study with larger sample size is neededfor widespread usage.